Characterization of the Effluent Organic Matter (EfOM) from the Domestic Wastewater Treated using Oxidation ditch and Microalgae Chlorella sp. - Emira Aulia Rachma; Euis Nurul Hidayah; Yuliatin Ali Syamsiah; Hirsandy Rachmadhany Alamsyah (Future Science)
Many advantages are obtained in treatment using microalgae. Microalgae treatment using an oxidation ditch can remove organic matter in wastewater. On the other side, the wastewater treatment using microalgae with oxidation ditch algae reactor (ODAR) to reduce organic matter also produces by-products that are harmful if dissolved in water. Processing in ODAR has Effluent Organic Matter (EfOM) and Algae Organic Matter (AOM) which are by-products of the microalgae process. The content of these compounds can lead to the formation of DBPs in water. This research was conducted on control variation (without microalgae) and variation of the volume of waste and microalgae 1:3, with oxic and oxic-anoxic conditions. Spectroscopy FTIR test is used to determine the organic matter contained through its functional groups. In the oxic-anoxic control variation, the FTIR percentage increased to 46.63% on the fifth day. In control oxic variation, it decreased to 46.12%. Meanwhile, in the oxic-anoxic 1:3 variation, the percentage decreased on the fifth day to 46.39%, and in oxic conditions, the rate was 46.8%. From the results obtained, the addition of microalgae can increase the content of organic matter in processing due to the by-products produced by microalgae and bacteria in processing.